2017
DOI: 10.1007/978-1-4939-7265-4_1
|View full text |Cite
|
Sign up to set email alerts
|

Super-Resolution Microscopy Techniques and Their Potential for Applications in Radiation Biophysics

Abstract: Fluorescence microscopy is an essential tool for imaging tagged biological structures. Due to the wave nature of light, the resolution of a conventional fluorescence microscope is limited laterally to about 200 nm and axially to about 600 nm, which is often referred to as the Abbe limit. This hampers the observation of important biological structures and dynamics in the nano-scaled range ~10 nm to ~100 nm. Consequentially, various methods have been developed circumventing this limit of resolution. Super-resolu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 82 publications
0
21
0
Order By: Relevance
“…The biological nature of the complex γH2AX/53BP1 focus clusters observed in the present study and the precise numbers of DSBs present in γH2AX/53BP1 foci/focus clusters (in general) therefore remain uncertain and must be further studied. Several recent reports [75][76][77][78] have suggested that super-resolution localization light microscopy offers an exciting but still challenging means of analysing the same biological specimens in parallel with confocal microscopy, but with much more detailed data. This strategy could be used to obtain answers to many questions discussed in this chapter in the near future.…”
Section: Discussionmentioning
confidence: 99%
“…The biological nature of the complex γH2AX/53BP1 focus clusters observed in the present study and the precise numbers of DSBs present in γH2AX/53BP1 foci/focus clusters (in general) therefore remain uncertain and must be further studied. Several recent reports [75][76][77][78] have suggested that super-resolution localization light microscopy offers an exciting but still challenging means of analysing the same biological specimens in parallel with confocal microscopy, but with much more detailed data. This strategy could be used to obtain answers to many questions discussed in this chapter in the near future.…”
Section: Discussionmentioning
confidence: 99%
“…Recent applications of electron-microscopy [25,26] and super-resolution light microscopy such as SMLM, STED or GSDIM [1,3,23,24,28,29,30,31,33,34] have demonstrated that it is feasible to study single molecular arrangements within a repair focus. With improving resolution of microscopy and data evaluation of structures on the meso- and nano-scale, the question for best suited analysis parameters and potentially useful classification criteria of repair foci and damaged chromatin sites has become important.…”
Section: Discussionmentioning
confidence: 99%
“…Nano-scaled analysis has reasoned several transmission electron and super-resolution light microscopic studies in order to elucidate the spatio-temporal internal organization of repair foci and their chromatin surroundings with molecular resolution [3,21,22,23,24,25,26,27,28,29]. Recently, it has been shown by super-resolution light microscopy, that γH2AX foci are built up by clusters that form nano-foci with different repair activities [23,28] and that inside these nano-foci repair proteins are well organized [23,24,29] whereas the chromatin environment is interacting in a characteristic arrangement [28,30,31]. In addition, it has been shown that after radiation exposure and DNA damaging, Alu heteroduplexes may undergo Alu/Alu recombination into a single chimeric Alu element by NHEJ [32].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For examining the DSB-induced chromatin changes, confocal microscopy-based techniques are used in most of the studies, although over the last few years the high-throughput chromosome conformation capture technique (4C) and single cell microscopy were utilized to gain detailed insights about the protein interactions and cascades involved in the different repair pathways. 31,[59][60][61][62][63] A more detailed overview has raised more questions, which could be answered only at a single-cell level: how the different DNA repair pathways are chosen and how individual repair proteins are regulated to access the DNA repair site. Answering these questions requires a better resolution, most favourably in a single molecule detection level deeply into the mechanistic organization of the orchestrated repair focus.…”
Section: Quantitative Analysis Of Single Dbs Repair Focimentioning
confidence: 99%